Development and Introduction of Ecotourism in Pulantani Village - Muhammad Yunus (Borneo Community Development, 2021)
The program for the development and introduction of ecotourism in Pulantani village is implemented as a community service program in 2021. This work program aims to develop ecotourism in Pulantani village, Haur Gading sub-district, upstream river Utara district. The problem found in the object is the lack of public knowledge on how to develop tourism potential. the method used is participatory and facilitative. The project implementation team participated and also provided facilities in the form of planning and planning assistance for ecotourism in Pulantani village as well as promoting the introduction of purun woven crafts as one of the local wisdom-based crafts.              The programs that are being carried out are still in the form of initiating plans and designs that need to be optimized by the community and assistance from local government support so that this program can develop properly and can be an alternative business sector for the surrounding community.